Ambrosia Beetles, Platypus spp. (Insecta: Coleoptera: Platypodidae) - T. H. Atkinson (EDIS)
The family Platypodidae includes approximately 1,000 species, most of which are found in the tropics (Schedl 1972). Seven species of platypodids, all in the genus Platypus, are found in the United States, four of which occur in Florida. All species found in Florida are borers of trunks and large branches of recently killed trees and may cause economic damage to unmilled logs or standing dead timber. The most recent key to species was published 60 years ago (Chamberlin 1939), does not include all species known from the United States (Wood 1979), and has long been out of print. This document is EENY-174 (originally published as DPI Entomology Circular 321), one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2000. Revised: March 2004.